2011
DOI: 10.1002/anie.201006134
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Virus‐like Particles with Poly(2‐oxazoline)s

Abstract: Wrap it up! Highly efficient copper‐catalyzed click chemistry can cover virus‐like particles with functionalized poly(2‐oxazoline) chains without interparticle aggregation. The resulting core–shell structures are significantly more temperature‐stable than the native protein particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 65 publications
2
60
0
Order By: Relevance
“…Simultaneous crosslinking occurred only if the solvent had induced the formation of micelles prior to the application of UV irradiation; if the copolymer was soluble in the solvent (e.g., tetrahydrofuran), thiol-yne reactions/polymeranalogous functionalization could be still observed while crosslinking of the dissolved polymer chains did not take place. [196]. While pMeOx and pEtOx enabled single-point attachment only in the copper-catalyzed reaction, the other two copolymers allowed multiple-point attachment (because of the p n Pe ≡ Ox units) and yielded fully crosslinked core-shell structures of high thermal stability.…”
Section: Click-reactions Involving Alkinesmentioning
confidence: 99%
“…Simultaneous crosslinking occurred only if the solvent had induced the formation of micelles prior to the application of UV irradiation; if the copolymer was soluble in the solvent (e.g., tetrahydrofuran), thiol-yne reactions/polymeranalogous functionalization could be still observed while crosslinking of the dissolved polymer chains did not take place. [196]. While pMeOx and pEtOx enabled single-point attachment only in the copper-catalyzed reaction, the other two copolymers allowed multiple-point attachment (because of the p n Pe ≡ Ox units) and yielded fully crosslinked core-shell structures of high thermal stability.…”
Section: Click-reactions Involving Alkinesmentioning
confidence: 99%
“…It has already been shown that the modification of virus particles with polymers increases their stability, and therefore, even allows them to be transferred to an organic solvent without disassembling, being more tolerant towards elevated temperature [72]. This was also shown by intra-viral capsid cross-linking using a polymer with multiple alkyne-groups attached to the backbone, which was allowed to react with a surface modified bacteriophage QB containing several azide moieties [73]. Via a Cu-catalyzed "click" reaction, the surface was coated with the polymer that covalently connected the individual viral capsids in the case when one polymer reacted with several capsids.…”
Section: Virus-polymer Conjugatesmentioning
confidence: 99%
“…It must be noted that the acetylene group is susceptible to deprotonation and side reactions can occur upon termination with methanolic potassium hydroxide, which is a commonly used terminating agent for the CROP of 2-oxazolines. 34 The commercial availability of propargyl tosylate and the efficiency of the CuAAC click conjugation, made this route towards clickable PAOx very popular and many functionalities, including virus-like particles, 35 thermo-responsive dendrimers, 36 amino acids, 37 and cyclic peptides 38 have been coupled in a similar way (cfr. section 2.2).…”
Section: Synthesis Of Chain-end Clickable Poly(2-oxazoline)smentioning
confidence: 99%
“…Furthermore, the selfassembly of block copolymers consisting of incompatible blocks has been investigated for use in nanolithography. 42 Microphase-segregation of such block copolymers is controlled by the size and Click chemistry-based surface modification of icosahedral virus-like particles (VLP) was demonstrated by Jordan, Finn et al 35 Ligation of polymers on the VLP surface not only leads to enhanced bioavailability, but also allows for biological labeling. In this study, the thermal stability of the capsids was demonstrated to significantly increase by CuAAC coupling with chain-end and sidechain alkyne-functionalized PAOx, of which the latter showed the best results.…”
Section: Applications Of Chain-end Clickable Poly(2-oxazoline)smentioning
confidence: 99%